2020
DOI: 10.15446/rev.colomb.biote.v22n2.74090
|View full text |Cite
|
Sign up to set email alerts
|

Reactores Bioquímicos Pasivos: Una alternativa biotecnológica para la remediación de drenajes ácidos de mina

Abstract: El Drenaje ácido de mina (DAM) es actualmente el principal contaminante de las regiones mineras. Los reactores bioquímicos pasivos son una tecnología sostenible fácil de instalar que utiliza desechos agroindustriales de la región y puede operar en áreas remotas con poco mantenimiento. Además, son una tecnología limpia que involucra bioprocesos, reacciones químicas y precipitación de metales minimizando el impacto de los vertimientos ácidos sobre suelos y cuerpos de aguas. Los reactores bioquímicos pasivos son … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 97 publications
1
2
0
1
Order By: Relevance
“…This behavior has been previously reported for other dissolved metals presents in AMD (Doye & Duchesne, 2003;Farrell & Chaudhary, 2013). Adsorption processes removed dissolved heavy metals completely from AMD because the pH increase was not high enough for their removal by precipitation formation (Matlock et al, 2002;Petrilakova et al, 2014;Vasquez & Escobar, 2020;Zhang et al, 2018). The solubility of SO4 2-, present in the AMD, is controlled by gypsum precipitation (Geldenhuys et al, 2003); which begins its formation and precipitation process at low pH, where it has been reported that the precipitation process begins at pH > 3.75 (Gitari et al, 2008;Macías et al, 2017;Madzivire et al, 2011).…”
Section: Amd and Sms Characterizationsupporting
confidence: 81%
See 1 more Smart Citation
“…This behavior has been previously reported for other dissolved metals presents in AMD (Doye & Duchesne, 2003;Farrell & Chaudhary, 2013). Adsorption processes removed dissolved heavy metals completely from AMD because the pH increase was not high enough for their removal by precipitation formation (Matlock et al, 2002;Petrilakova et al, 2014;Vasquez & Escobar, 2020;Zhang et al, 2018). The solubility of SO4 2-, present in the AMD, is controlled by gypsum precipitation (Geldenhuys et al, 2003); which begins its formation and precipitation process at low pH, where it has been reported that the precipitation process begins at pH > 3.75 (Gitari et al, 2008;Macías et al, 2017;Madzivire et al, 2011).…”
Section: Amd and Sms Characterizationsupporting
confidence: 81%
“…Table I shows the physicochemical parameters of the AMD used in this work. As seen, AMD presents a high concentration of SO4 2and total Fe, characteristic of this type of drainage and the presence of heavy metals such as As 3+, 5+ , Cd 2+ , and Pb 2+ (Skousen et al, 2019;Vasquez & Escobar, 2020). A highly acidic pH is observed, set at pH = 2.25; additionally, the deficiency of DO (dissolved oxygen) allows cataloging the AMD as a hypoxic/anoxic fluid associated possibly with Fe 2+ concentrations higher than 63 mg•L -1 , which is capable of depleting the oxygen content in the AMD (Hustwit et al, 1992).…”
Section: Raw Materials Characterization 311 Amd Samplesmentioning
confidence: 84%
“…Physical methods, such as adsorption and filtration, employ materials such as limestone to adsorb and filter contaminants from water. These methods, applied appropriately, can significantly reduce acidity and toxic metals levels in waters affected by AMD (Vásquez and Escobar, 2020;Guadarrama, 2022;Jiménez, 2017;López, 2016). Calcium hydroxide, also known as hydrated lime, is an alkaline compound widely used in the neutralization of acidic waters due to its high water solubility properties and its ability to raise pH and precipitate heavy metals.…”
Section: Methods Of Acid Water Remediationmentioning
confidence: 99%
“…Los reactores bioquímicos pasivos son columnas empacadas con una mezcla reactiva conformada por materiales orgánicos, inorgánicos y un inóculo microbiano. Esta mezcla es usada para corregir el drenaje acido minero por medio de procesos fisicoquímicos como la adsorción, precipitación de los metales y de la reducción del sulfato a sulfuro, mientras se incrementa el pH y la alcalinidad [12].…”
Section: Métodos De Remediación De Pasivos Ambientales Minerosunclassified